PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION DISERTAI NUMBERED HEADS TOGETHER TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMA NEGERI 2 BAYANG - Elpajriani, Wenda; Rahmi, Rahmi; Lovia, Lita (Pendidikan Matematika, 2014)
Â ABSTRACTÂ This research is motivated by less students are responsible for completing the tasks assigned teacher and students are less motivated to follow the learning of mathematics as well as students understanding of mathematical concepts are still low. This research aims to determine whether students understanding of mathematical concepts by implementing Student Team Achievement Division (STAD) with Numbered Heads Together (NHT) cooperative learning model better understanding of the mathematical concepts of the conventional learning in class XI IPA SMAN 2 Bayang. This was an experimental research which used random research design toward the subject. The instrument used in this research is a test in studentsâ understanding on mathematics concept. Based on the result of data analysis, it was revealed that the sample was distributed normally and had homogeny variant. Hypothesis test results obtained t = 2,71 was bigger than ,Â  indicating that the hypothesis was accepted. So, it was concluded that the application of STAD with NHT cooperative learning model could improve the studentsâ understanding on mathematics concept, and better than the conventional one.